Management of Subclinical and Overt Hypothyroidism Following Hemithyroidectomy in Children and Adolescents: A Pilot Study - Chen, Jiarui; Hou, Shule; Li, Xiaoyan; Yang, Jun (Frontiers in Pediatrics, 2019)
Background: Hemithyroidectomy is preferred in children and adolescents with benign nodular thyroid disease to decrease surgical complications and prevent lifelong thyroid hormone replacement. However, hypothyroidism following hemithyroidectomy may occur, and postoperative thyroid hormone replacement for hypothyroidism following hemithyroidectomy is usually administered without fully understanding the clinical characteristics of hypothyroidism. Methods: To identify the incidence and risk factors for hypothyroidism after hemithyroidectomy in children and adolescents and to determine whether postoperative thyroid hormone replacement is necessary. A retrospective was reviewed of forty-three patients under 18 years of age who underwent hemithyroidectomy from January 2009 to October 2016. All hypothyroid patients were reviewed to determine the frequency of postsurgical hypothyroidism and the predisposing factor(s). All patients were evaluated for age, gender, serum thyrotropin (TSH), antithyroid antibody and histological evidence of lymphocytic infiltration. Hypothyroid patients were evaluated for symptoms, timing of diagnosis, and thyroid hormone replacement. Results: The mean age at the time of surgery was 13.65±3.04 years. 34 females (79.07%), the mean follow-up time was 28±9 months. Hypothyroidism was diagnosed in 11 of the 43 patients. The mean postoperative TSH level was 7.17±2.13 µIU/ml. The mean preoperative TSH level was 3.11±0.59 µIU/ml in hypothyroid patients compared with 1.92±0.72 µIU/ml in euthyroid patients (P˂0.05). A preoperative TSH level >2.2 µIU/L and lymphocytic infiltration graded 3 or 4 were found to be independent risk factors for the development of hypothyroidism. There were no significant differences between groups in terms of patient age or gender. Conclusions: In the pediatric and adolescent population, patients with elevated preoperative TSH levels or the presence of lymphocytic infiltrates may be at an increased risk of hypothyroidism. In our study, postoperative levothyroxine (L-T4) treatment was necessary in 16.28% of cases after hemithyroidectomy. Patients with mild postoperative hypothyroidism should be followed-up without immediate L-T4 replacement with the expectation of spontaneous recovery.